2021
DOI: 10.48550/arxiv.2111.05358
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On the Effect of the Large Magellanic Cloud on the Orbital Poles of Milky Way Satellite Galaxies

Marcel S. Pawlowski,
Pierre-Antoine Oria,
Salvatore Taibi
et al.

Abstract: The reflex motion and distortion of the Milky Way (MW) halo caused by the infall of a massive Large Magellanic Cloud (LMC) was shown to result in an excess of orbital poles of dark matter halo particles towards the LMC orbital pole. This was suggested to help explain the observed preference of MW satellite galaxies to co-orbit along the Vast Polar Structure (VPOS), the MW's satellite plane. We test this idea by correcting the positions and velocities of the MW satellites for the Galactocentric-distancedependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Previous work has found that the MW dSphs share a common orientation and that it may be related to the Vast Polar Orbital structure (Sanders & Evans 2017). The Vast Polar Orbital structure and orbital poles alignment may be caused by the LMC (Garavito-Camargo et al 2021) but Pawlowski et al (2021) show the magnitude of the LMC perturbation is to small to fully explain the Vast Polar Orbital structure. Overall, we find excellent agreement between our results and other Gaia EDR3 proper motion results 3 (Mc-Connachie & Venn 2020b; Li et al 2021;Martínez-García et al 2021;Vitral 2021;Battaglia et al 2022;Qi et al 2022).…”
Section: Is Orientation a Signature Of Tidal Disruption?mentioning
confidence: 95%
“…Previous work has found that the MW dSphs share a common orientation and that it may be related to the Vast Polar Orbital structure (Sanders & Evans 2017). The Vast Polar Orbital structure and orbital poles alignment may be caused by the LMC (Garavito-Camargo et al 2021) but Pawlowski et al (2021) show the magnitude of the LMC perturbation is to small to fully explain the Vast Polar Orbital structure. Overall, we find excellent agreement between our results and other Gaia EDR3 proper motion results 3 (Mc-Connachie & Venn 2020b; Li et al 2021;Martínez-García et al 2021;Vitral 2021;Battaglia et al 2022;Qi et al 2022).…”
Section: Is Orientation a Signature Of Tidal Disruption?mentioning
confidence: 95%
“…But, as mentioned above, the actual global response of the DM halo (and, subsequently, of the stellar halo) is more subtle than that, and depends on the underlying distribution of DM in phase-space, as studied by, e.g., Laporte et al (2018); Garavito-Camargo et al (2019); Garavito-Camargo et al (2021a); Tamfal et al (2021). It has for instance been shown that the LMC could induce an overdensity in the orbital poles of particles moving through the halo (Garavito-Camargo et al 2021b), although it has been subsequently shown that the effect was only present for particles with low specific angular momentum (Pawlowski et al 2021).…”
Section: Introductionmentioning
confidence: 99%